Radio Frequency Propagation Mechanisms and Empirical Models for Hilly Areas - Famoriji John O; Olasoji Yekeen O (Institute of Advanced Engineering and Science, 2013)
Achieving better network performance is a paramount concern in wireless networks. This paper provides a survey of the basic mechanisms which influence the propagation of electromagnetic waves in hilly areas. Three empirical models: COST231-Hata, Okumura-Hata and Egli which are suitable for path loss prediction for such area are presented. By using these propagation models the broadcast signal strength are predicted for this type of environment. Measurement results of signal strength in UHF band obtained in Idanre Town of Ondo State Nigeria are presented and compared with the results predicted by using the propagation models. A modified COST231-Hata radiowave propagation model was developed and implemented with Matlab GUI (Graphical User Interface) for simulation. The model developed has 93.8% accuracy.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2519